1 Peripheral blood natriuretic peptide is associated with myocardial fibrosis and cardiac tissue expression of natriuretic peptide and fibro-inflammatory genes in patients with normal ejection fraction. (28th September 2016) - Watson, C; Collier, P; Phelan, D; Glezeva, N; Baugh, J; McDonald, K; Ledwidge, M
Abstract : Introduction: The St Vincent's Screening TO Prevent Heart Failure (STOP-HF) study showed that preclinical left ventricular diastolic dysfunction (PCDD) is more prevalent than left ventricular systolic function, that peripheral blood natriuretic peptide (NP) can be used to identify asymptomatic myocardial disease and that NP correlates with disease severity. Methods: We investigated peripheral blood biomarkers associated with PCDD and corresponding myocardial gene expression of the biomarkers in 35 consecutive, consenting stable patients with normal ejection fraction (EF > 45%) undergoing elective CABG surgery. Atrial tissue was obtained adjacent to the venous cannulation site and was stained for collagen using picosirus red and macrophage markers. Patients were categorised as PCDD or controls based on Doppler Echocardiography. Biomarkers and genes of interest included fibro-inflammatory genes, NP and its main transmembrane receptor Natriuretic Peptide Receptor A (NPRA). Results: Patients were aged 67.4 ± 9.8 years, 25 (69%) were male, 18 (53%) had hypertension and 5 (14%) had diabetes. Preclinical LVDD patients (n = 10) had greater tissue collagen volume fraction, E/Eprime (12.5 ± 2.6 vs. 8.4 ± 2.0), LAVI (30.6 ± 4.2 vs. 27.8 ± 3.4) and atrial fibrillation (70% vs 8%) than controls (all p < 0.05). PCDD was associated with increased myocardial gene expression of collagen 1, collagen 3, MMP2, TNFalpha, Thy1, LOX, Ferritin and RPCP. M2 Macrophage marker CD163 was strongly correlated with collagen 1 and 3 expression as well as myocardial expression of BNP and NPRA. BNP levels were significantly higher in preclinical LVDD patients (163 ± 147 vs. 57 ± 85, p < 0.01) but no other peripheral blood biomarkers of inflammation, collagen turnover or extracellular matrix turnover differed between the groups. BNP was the only blood biomarker that correlated with myocardial expression of the corresponding gene. Conclusion: PCDD is associated with elevated peripheral blood NP, myocardial fibrosis and altered expression of fibro-inflammatory genes in the myocardium. Unlike other markers of fibro-inflammation, peripheral blood NP was correlated with myocardial tissue expression of its corresponding gene and these data underline the value of peripheral blood NP in risk stratification in PCDD.